The orthopaedic provision for patients with osteoarthrosis of the knee joints - Andrukhova, Raisa; Boboshko, Ruslan; Nedilko, Yurеy; Zaitsev, Michail; Pivovarov, Victor; Baev, Pavel (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The authors present the results of their study of 149 patients with different degrees of intensity of their knee joint osteoarthrosis. The orthopaedic provision for patients with degrees I-IV of osteoarthrosis is described in detail. Satisfactory and good results were obtained in 93 % of cases.